EDUKASI MANAJEMEN KOPING PENCEGAHAN DAN TATALAKSANA DEPRESI POST PARTUM - Indah Lestari (Bajang Institute, 2023)
Postpartum depression is a serious condition, especially for mothers who are giving birth for the first time or mothers with sibling conditions who have not been prepared. The impact that occurs on the mother and baby should be prevented with good management. The purpose of this community service is to provide education on coping management about the prevention and management of postpartum depression, for postpartum mothers in collaboration with the Punggul-Mojokerto Village Polindes Midwife. Implementation of activities in January 2023, starting from the preparation stage to the evaluation stage. The output of the activity is an increase in the understanding of postpartum mothers, the readiness of mothers to undergo childbirth, and new roles. In efforts to improve maternal and child health, modules and booklets are available related to postpartum and newborn care, with the hope that reproductive mothers will increase their knowledge about maternal issues